Food Preferences of Mediterranean Cold-Water Corals in Captivity - Da Ros, Zaira; Dell’Anno, Antonio; Fanelli, Emanuela; Angeletti, Lorenzo; Taviani, Marco; Danovaro, Roberto (Frontiers in Marine Science, 2022)
Cold-water coral (CWC) systems are hotspots of biodiversity that need protection from the increasing human impacts and global climate change. The restoration of degraded cold-water coral reefs may be conducted through transplantation of nubbins. To do so, we need to set up the optimal conditions for CWCs livelihood in an aquarium setting. Here we investigated the food selection of three cold-water coral species, inhabiting the NE Atlantic Ocean and the Mediterranean Sea, to identify the optimal feeding conditions to rear corals, by means of stable isotope analysis (δ15N and δ 13C) and of prey-capture rates. Colonies of Desmophyllum pertusum, Madrepora oculata and Dendrophyllia cornigera were collected in the Mediterranean Sea and nourished in mesocosms with a) nauplii of Artemia salina, b) the green algae Tetraselmis subcordiformis, c) two rotifer species (Brachionus plicatilis and B. rotundiformis) and d) mysids of the species Mysis relicta. Prey-capture rates coupled with isotope analysis revealed that M. relicta was the preferred food source even if it was provided as a frozen item, followed by the live-items A. salina and Brachionus spp. Isotopic analyses allowed to determine that POM appears to be contributing a large portion of the isotopic composition of the coral tissue and suggested also that M. oculata has the most opportunistic behaviour among the three target coral species. This study confirms that it is possible to optimize CWCs livelihood in aquaria choosing the right food sources during their maintenance also in preparation to their transplant in degraded habitats during future projects of active restoration.